Becoming Lean : Inside Stories of U.S. Manufacturers - Gérin-Lajoie, Jean (Relations industrielles / Industrial Relations, 2001)
The article reviews the book, "Becoming Lean : Inside Stories of U.S. Manufacturers," edited by Jeffrey K. Liker.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; Management; Manufacturers; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z